Activities manual for programmable logic controllers - Petruzella, Frank D. (McGraw-Hill Higher Education, 2005)
The Activities manual contains true/false, completion, matching, and multiple-choice questions for every chapter in the text. So that students get a better understanding of programmable logic controllers, the manual also includes a wide range of programming assignments and additional practice exercises.